Haematopoietic stem cell transplantation for inborn errors of immunity: 25‐year experience from University of Malaya Medical Centre, Malaysia. (3rd September 2019) - Ariffin, Hany; Ab Rahman, Syaza; Jawin, Vida; Foo, Jen Chun; Amram, Nur Faizana; Mahmood, Nur Mahirah; Yap, Tsiao Yi; Rajagopal, Revathi; Lum, Su Han; Chan, Lee Lee; Lin, Hai Peng
Abstract : Aim: Inborn errors of immunity (IEI) comprise a heterogeneous group of disorders of the immune system, most of which are curable by haematopoietic stem cell transplantation (HSCT). We present a 25‐year audit of HSCT for IEI at a tertiary‐level academic hospital in Malaysia. Methods: Review of medical records of all cases of IEI who underwent HSCT between January 1993 and December 2018 at our centre. Diagnoses, complications, HSCT protocols and outcome data were studied. Results: There were 20 patients (19 boys) with a median age at diagnosis of 11 months (range: 2 months to 12 years). Eleven of 19 (58%) had malnutrition at presentation. Donor sources were variable: 13 (65%) matched sibling donor (MSD), 4 (20%) human leukocyte antigen‐haploidentical donor (HD) and 3 (15%) matched unrelated donor (MUD). Conditioning regimens were physician‐dependent and adapted to each patient's clinical status. Grades III–IV acute graft‐versus‐host disease occurred in two of three cases who received MUD grafts, 50% in those who received HD, and 8% in the MSD group. Transplant‐related mortality at day +100 was 5%. With a median follow‐up of 7.5 years, 18 (90%) patients are alive and free of infections. Conclusion: Outcome of HSCT for IEI in our centre is comparable with international reports. HSCT results using HD and MUD grafts are also good despite challenges from acute graft‐versus‐host disease, providing a feasible alternative for patients without matched donors.